Procoagulant Microparticles in Dogs with Immune‐Mediated Hemolytic Anemia. (13th April 2015) - Kidd, L.; Geddings, J.; Hisada, Y.; Sueda, M.; Concannon, T.; Nichols, T.; Merricks, E.; Mackman, N.
<x xml:space="preserve">Abstract</x> Background Studies of some human prothrombotic diseases suggest that phosphatidylserine‐positive (PS+) and tissue factor‐positive (TF+) microparticles (MPs) might play a role in the pathogenesis of thrombosis or serve as biomarkers of thrombotic risk. Hypothesis/Objectives To determine if circulating levels of PS+MP and procoagulant activity (PCA) associated with PS+MPs and TF+ MPs are increased in dogs with IMHA. Animals Fifteen dogs with primary or secondary IMHA and 17 clinically healthy dogs. Methods Prospective case‐controlled observational study. Circulating PS+MPs were measured by flow cytometry. PCA associated with PS+MPs and TF+MPs was measured by thrombin and Factor Xa generating assays, respectively. Results Circulating numbers of PS+MPs were not significantly higher in dogs with IMHA [control median 251, 000/μL (36, 992–1, 141, 250/μL); IMHA median 361, 990/μL (21, 766–47, 650, 600/μL) P = .30]. However, PS+MP PCA [control median 2.2 (0.0–16.8) nM PS eq; IMHA median 8.596, (0–49.33 nM PS eq) P = .01] and TF+MP PCA [control median 0.0, (0.0–0.0 pg/mL); IMHA median 0.0; (0–22.34 pg/mL], P = .04) were increased. Intravascular hemolysis, which we showed might increase PS+ and TF+MP PCA, was evident in 3 of 5 dogs with PS+MP PCA and 2 of 4 dogs with TF+MP PCA higher than controls. Underlying disease in addition to IMHA was detected in 1 of 5 dogs with PS+PCA and 3 of 4 dogs with TF+MP PCA higher than controls. Conclusions and Clinical Importance TF+ and PS+MP PCA is increased in some dogs with IMHA. Further studies that determine if measuring TF+ and PS+ MP PCA can help identify dogs at risk for thrombosis are warranted.